Spiritual Well-Being with Sleep Quality of Chronic Kidney Disease Patients on Hemodialysis - Giri Susanto; Mesya Mesya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hemodialysis can cause side effects such as difficulty falling asleep, patients with kidney disease view Spritual Well-Being as a multidimensional concept that combines physical and psychological health. This study aims to determine the correlation between spiritual well-being and sleep quality of chronic kidney disease patients undergoing hemodialysis. This study is a type of quantitative research using a cross-sectional design, the research subjects are patients with kidney disease who undergoing hemodialysis with sleep quality disorders, with a total population of 176 patients with sampling techniques using purposive sampling with a sample size of 64 respondents, research at Pringsewu Hospital. Data collection using the Spiritual Well-Being Questionnaire and PSQI Questionnaire, data analysis using the Chi Square Test. The results showed that most respondents with High Spiritual Well-Being were 35 (54.7%), and most respondents with good sleep quality were 36 (56.2%), statistical tests showed that there was a correlation between Spiritual Well-Being and Sleep Quality of Chronic Kidney disease Patients Undergoing Hemodialysis at Pringsewu Hospital with a P-value: 0.000. The results of this study are expected to be a material for learning and deeper knowledge about spiritual well- being and sleep quality of chronic kidney disease patients undergoing hemodialysis.